PENGARUH GAYA BERENANG (GAYA BEBAS DAN GAYA DADA) TERHADAP PERUBAHAN VOLUME OKSIGEN MAKSIMUM - Dennison, Dennison; Sriwahyuni, Endang; Wardhani, Viera (Fakultas Kedokteran Universitas Brawijaya, 2003)
ABSTRACT Swimming is frequently used to improve the individual physical endurance. Most of the studies have proved that swimming can improve the maximum oxygen volume effectively, but none of them compare the differences in the swimming styles. The study was aimed to analyse the differences of swimming styles in improving maximum oxygen volume, so it can be used as basis for physical training scheme. A pretest-posttest experimental design was conducted in two sample group (front crawl stroke group and breast stroke group) consists of six people in each group. The samples were selected based on questionaire to control the confounding variables, ie: sex, age, height, weight, training habit and health status (anemia, heart disease and respiratory distress). The training method were carried out in 12 session in 4 weeks (3 session per week) by increasing the swimming distance gradually. Each session arrangement was consists of warming up - training in short sets with rests - relaxation. The maximum oxygen volume was measured using Cooper method and the result was analyzed using independent sample t-test with SPSS 11. The result shows that there is a significant difference in maximum oxygen volume improvement (t= -4.718, CI 95% = lower: -5.014; upper: -1.722, p= 0.002) in which the result in breast stroke group has a higher improvement (mean: 6.313, sd: 1.378)